Power of Taxation over Income of Employees of Public Enterprises Owned by the Federal Government of Ethiopia: A Case Comment - Ashagre, Aschalew Byness (Bahir Dar University Journal of Law, 2022)
According to the Amharic version of Article 96(3) of the FDREConstitution,8 the Federal Government of Ethiopia has the power to levy andcollect income tax on employees of the public enterprises it owns. Despitethis, there are sometimes misunderstandings regarding the message conveyed by this article, probably due to the fact that there is no parity between theAmharic and the English versions of this provision. Such a misunderstandingmanifested itself in a case that cropped up between Fidelitu WoredaFinance, Economic Development and Revenue Office, Liben Zone, SomaliRegional State9 (hereinafter cited as the respondent) and the Federal WaterWorks Construction Enterprise (a public enterprise hereinafter cited as theapplicant), owned by the Federal Government of Ethiopia. In this case, courtsof all levels10 in the Somali Region decided that income tax collected from theemployees of this enterprise belonged to the Somali National Regional State.The case was finally submitted to the Cassation Division of the FederalSupreme Court of Ethiopia (hereinafter cited as the Cassation Division),which reversed the decisions of the regional courts. As we will see below, theCassation Division handed down a correct and acceptable decision, supportedby the relevant provisions of the FDRE Constitution.